Serial T2-Weighted Thoracic and Abdominal Lymphatic Imaging in Fontan Patients—New Insights into Dynamics of Lymphatic Abnormalities after Total Cavopulmonary Connection - Moosmann, Julia; Schroeder, Christian; Rompel, Oliver; Purbojo, Ariawan; Dittrich, Sven (Journal of Cardiovascular Development and Disease, 2022)
Lymphatic congestion in single-ventricle patients has been associated with increased morbidity and poor outcomes. Little is known about the dynamics of lymphatic abnormalities over time, on their association with clinical presentation or response to catheter interventions. This retrospective, single-center study describes Fontan patients who underwent at least two magnetic resonance imaging (MRI) studies. T2-weighted lymphatic imaging was used to classify thoracic and abdominal (para-aortic and portal-venous) lymphatic abnormalities. The relationship between lymphatic congestion and hemodynamic changes after cardiac catheter interventions, clinical presentation and MRI data was analyzed. A total of 33 Fontan patients underwent at least two cardiac MRI studies. Twenty-two patients had two, eight had three and three had four lymphatic imaging studies (total of 80 MRIs studies). No significant changes in lymphatic classification between MRI 1 and 2 were observed for thoracic (p = 0.400), para-aortic (0.670) and portal-venous (p = 0.822) abnormalities. No significant correlation between lymphatic classification and hemodynamic changes after intervention or MRI parameters was found. This study illustrates thoracic and abdominal lymphatic abnormalities in serial T2-weighted imaging after Fontan. Fontan patients did not demonstrate significant changes in their lymphatic perfusion, despite clinical or hemodynamic changes. We assume that lymphatic congestion might develop after total cavopulmonary connection (TCPC) and remain relatively stable, despite further intervention targeting hemodynamic parameters.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Fontan; lymphatic abnormalities; magnetic resonance imaging; T2-weighted imaging